Accelerating haploid induction rate and haploid validation through marker-assisted selection for qhir1 and qhir8 in maize - Khammona, Kanogporn; Dermail, Abil; Suriharn, Khundej; Lübberstedt, Thomas; Wanchana, Samart; Thunnom, Burin; Poncheewin, Wasin; Toojinda, Theerayut; Ruanjaichon, Vinitchan; Arikit, Siwaret (Frontiers in Plant Science, 2024)
Doubled haploid (DH) technology becomes more routinely applied in maize hybrid breeding. However, some issues in haploid induction and identification persist, requiring resolution to optimize DH production. Our objective was to implement simultaneous marker-assisted selection (MAS) for qhir1 (MTL/ZmPLA1/NLD) and qhir8 (ZmDMP) using TaqMan assay in F2 generation of four BHI306-derived tropical × temperate inducer families. We also aimed to assess their haploid induction rate (HIR) in the F3 generation as a phenotypic response to MAS. We highlighted remarkable increases in HIR of each inducer family. Genotypes carrying qhir1 and qhir8 exhibited 1 -3-fold higher haploid frequency than those carrying only qhir1. Additionally, the qhir1 marker was employed for verifying putative haploid seedlings at 7 days after planting. Flow cytometric analysis served as the gold standard test to assess the accuracy of the R1-nj and the qhir1 marker. The qhir1 marker showed high accuracy and may be integrated in multiple haploid identifications at early seedling stage succeeding pre-haploid sorting via R1-nj marker.